Enola's Personality in the Enola Holmes Movie Using Jungian Archetype Theory - Manullang, Elisa Betty; Mestika, Angel (East Asian Journal of Multidisciplinary Research, 2024)
The intriguing facets of Enola Holmes' character in the eponymous film, encompassing her intelligence, independence, resourcefulness, and defiance of societal norms, have captured the researchers' interest, prompting a comprehensive exploration using an archetypal framework. This research aims to unravel the symbolic patterns that shape Enola's identity and, in turn, enlighten people about the diverse facets of human character and individuality. The researchers utilized a qualitative descriptive methodology, delineating the research design encompassing procedures such as watching, data gathering, classification, identification, and contextual as well as theoretical analysis of monologues and dialogues within the movie. The subject of the research was the protagonist of the Enola Holmes movie. The results indicated that among 51 data samples, five archetypal types were identified, including self, ego, persona, shadow, and animus. The most prevalent archetype in Enola's character is animus, highlighting her portrayal as a woman with masculine characteristics. The shadow archetype plays a minimal role in her personality, signifying that Enola embodies her internal desires and nonconformist elements.